Characterization of Eperythrozoon Ovis Isolated From Sheep and Goats in Malaysia - Ershaduzzaman, Md. (2001)
The characteristics of Eperythrozoon ovis isolated from sheep and goats blood were studied by several approaches. Detection of E. avis from naturally infected sheep and goats was compared by light microscopy, scanning electron microscopy (SEM), transmission electron microscopy (TEM), indirect immunofluorescent antibody test (IFAT) and confocal microscopy. It was concluded that the Giemsa staining is cheap, fast and easy to perform, but it may not be specific when E. ovis become difficult to distinguish from stain deposits or dust particles. The IFAT was rapid, specific and sensitive, but it required specific hyperimmune serum and sometimes it produced background glow that degrades the images. The confocal microscopic examination greatly enhanced images of E. ovis and was more sensitive than IFAT. The SEM and TEM are indispensable tools for the unambiguous identification of H. ovis morphology and it also provide ultrastructural detail of the organism. In vitro culture and maintenance of E. ovis was successfully done upto 408 hours in tissue culture media. After intensive screening, the following conditions were found to be optimal for maintenance of red blood cell attachment by E. ovis, heparin as the anticoagulant for blood collection, incubation with Eagle's medium under 5% C02 and supplemented with inosine and foetal calf serum, and refreshment of medium every 12 hours. An attempt to propagate F. ovis in 8 days old embryonated chicken eggs by inoculating through the yolk sac, chorioallantoic membrane and allantoic sac was carried out. Infectivity was checked impression smears made from organs (liver, spleen and yolk sac membrane) of dead and live embryoes and stained with Giemsa and further confirmed by IFAT. Among the three routes of inoculation, yolk sac was the most suitable route for propagation of E. ovis. Large number of E. ovis organisms were seen in yolk sac membrane. Western blotting analysis of the purified sample using hyperimmune serum prepared by injecting purified E. ovis antigens collected from infected sheep into rabbits, revealed five protein bands with MW 180, 172, 118, 95 and 80 kDa were identified as the E. ovis specific bands. Among the 5 selected proteins MW 95 kDa was the most dominant. These protein were detected from infected sheep and goats indicating that the protein profiles of E. ovis isolated from sheep and goats were similar. Polymerase chain reaction (PCR) of the 16S rRNA gene was investigated to determine its potential as a means of detecting E. ovis infection in sheep and goats. PCR produced a specific product of approximately 1500 bp from infected but not uninfected samples. Sensitivity studies indicated that the peR protocol was capable of amplitying total genomic E. ovis DNA in quantities as low as 20 ng. In conclusion, this study discussed for the first development of PCR based assay to detect E. ovis from naturally infected sheep and goats. It seems that the PCR assay is specific and very sensitive compared to other test. Development of in vitro maintenance study provides information about the establishment of in vitro culture system for the maintenance and propagation of E. ovis. This study also indicated that the protein profiles of E. ovis isolated from sheep and goats were similar.